STRATEGI KOMUNIKASI PEMASARAN CAFE TONG SUSU PEKANBARU DALAM MENINGKATKAN JUMLAH KONSUMEN - Septian, Deddy; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Pekanbaru is the strategic areas where the population is increasing and becoming a metropolitan city. Pekanbaru rapid development is also reflected in the rapid growth of existing businesses in various places with various products. Certainly many cafes in pekanbaru like: Cafe D’Neneners, Cafe House Milk, Re Caffe, Fluffy Cafe, Bier Hause Cafe, Cafe Excelso, etc. The presence of other cafes as competitors who sell fresh milk to make Cafe Tong Susu Pekanbaru should strive to increase the number of consumers in addressing the decline in consumers. Therefore, researchers interested in conducting research in order to determine the marketing communication strategy Tong Susu Cafe Pekanbaru in increasing the number of consumers.This study used qualitative methods, collecting data obtained based on the reality in the field of data through observation, interviews, and documentation. The subjects were 1 Owner, 1 manager, 8 consumers, and 4 prospective customers Tong Susu Cafe Pekanbaru are selected using purposive sampling technique. To analyze the results of this study using interactive data analysis techniques, while data validity checking techniques through extension of participation and triangulation.The results showed that the strategy of marketing communications Cafe Tong Susu Pekanbaru in increasing the number of consumers Sales promotion activities for promo new menus and discounts. Personal selling activities do live presentations, invited presentations and headed presentation. Activities performed on publicity by publishing logos Tong Susu Cafe Dairy Milk through the cars scattered Pekanbaru city areas while the public relations activities to socialize directly with consumers and potential consumers Tong Susu Cafe Pekanbaru.Direct marketing activities carried out by using that phone, SMS (Short Message Service), and Twitter Mentions. Lastly,is the through Internet Marketing Media using facebook and Twitter social mediaKeywords: Marketing Communication Strategy, Increase Consumers Number, Cafe.